Progress and challenges in genome-wide studies to understand the genetics of diabetic retinopathy - Burdon, Kathryn P.; McComish, Bennet J.; Charlesworth, Jac C. (Annals of Eye Science; Vol 3 (August 2018): Annals of Eye Science, 2018)
There are many advantages to understanding the genetics of human disease. Genetic markers can be used to calculate the risk of developing a disease, and elucidation of genetic risk factors can pinpoint the molecular aetiology of disease, which can facilitate the development of targeted therapies. Diabetic retinopathy (DR) is a common complication of diabetes that has a significant impact on quality of life. It has a clear genetic component, but determination of the genetic risk factors has proven difficult. To date, genome-wide studies for DR have been conducted on relatively small patient cohorts compared to other complex eye diseases and replication of genetic findings has been limited. The disease is highly heterogeneous, confounding attempts to classify patients into appropriate groups for genetic analysis and making direct comparisons between studies challenging. Future studies to determine the genetic causes of DR will need to focus on larger sample sizes, detailed phenotyping and appropriate classification of patients. Global co-operation and meta-analyses combining data from multiple studies will be critical to the discovery of genetic risk loci for DR.